The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fimmu.2021.639672
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of CDR3 Sequences in Gluten-Specific T-Cell Receptors Reveals a Dominant R-Motif and Several New Minor Motifs

Abstract: Gluten-specific CD4+ T cells are drivers of celiac disease (CeD). Previous studies of gluten-specific T-cell receptor (TCR) repertoires have found public TCRs shared across multiple individuals, biased usage of particular V-genes and conserved CDR3 motifs. The CDR3 motifs within the gluten-specific TCR repertoire, however, have not been systematically investigated. In the current study, we analyzed the largest TCR database of gluten-specific CD4+ T cells studied so far consisting of TCRs of 3122 clonotypes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
(53 reference statements)
0
29
1
Order By: Relevance
“…In the future, our work could be extended to consider family-wise or false discovery error rates, as has been done for RNA sequencing [ 31 , 35 ]. Such an extension would allow for the quantification of detection power to entire sets of TCRs, which is especially relevant when considering ‘public’ TCR sets that are shared across many individuals [ 6 , 16 , 41 ]. Finally, our read count model could also be used to generate synthetic TCR sequencing repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, our work could be extended to consider family-wise or false discovery error rates, as has been done for RNA sequencing [ 31 , 35 ]. Such an extension would allow for the quantification of detection power to entire sets of TCRs, which is especially relevant when considering ‘public’ TCR sets that are shared across many individuals [ 6 , 16 , 41 ]. Finally, our read count model could also be used to generate synthetic TCR sequencing repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the current knowledge about immunosenescence and TCR repertoire dynamics in autoimmune and T-cell mediated diseases is still quite fragmented. In RA ( 15 , 36 39 ), CD ( 49 53 ) and T1D ( 59 61 ) patients, different compartments (blood, synovia, gut, pancreatic draining lymph nodes) share TCRβ clones and show reduced TCR repertoire diversity. Furthermore, immunosenescence seems to be accelerated in RA patients ( 15 , 42 44 ), and T1D severity is aggravated in older patients ( 58 ); however, most of these studies are not centered on an age-related perspective, stressing for further insights.…”
Section: Discussionmentioning
confidence: 99%
“…HTS on single-cell gut IELs TCRγδ showed that CD patients, either under GFD or not, have a biased TRDV pattern compared to healthy controls, a private CDR3δ repertoire, whereas CDR3γ clones are shared between CD and controls ( 52 ). A recent investigation leveraging a large TCRαβ dataset of data from 63 CD patients ( 53 ) identified a number of 325 public TCRαβ clones in gluten-specific CD4+ T cells across patient; furthermore, they observed a biased V-gene usage and conserved CDR3α:CDR3β motifs across CD repertoires. Taken together, these findings indicate that TCR repertoire shares common features across CD patients that may be linked to disease pathogenesis and progression; however, the association between TCR repertoire dynamics, T-cell senescence and aging in CD is still not deeply investigated.…”
Section: Senescent T-cell Receptor Repertoire In Autoimmune Disorders: Progresses and Perspectivesmentioning
confidence: 99%
“…Two of these 12 shared sequences were found in the collection of public, gluten-specific TCR sequences. Six of the 12 shared TCR sequences were represented among the generated O, [25] ; 13 AV41_AVEGGSNYKLT_AJ53 O, [25] ; 10 BV7-2_ASSIRATDTQY_BJ2-3 R1 O, [25] ; 9 BV7-3_ASSIRSTDTQY_BJ2-3 NR1 O, [25] ; 14 BV20-1_SASRTSGRAGDEQF_BJ2-1 O, [26] The grey filling represents patients that express the indicated public TCR sequences. Some sequences were expressed by T cell clones (TCCs) that were tested for gluten reactivity.…”
Section: Ttet − /Tphe + Cells Demonstrate Clonal Expansion and Sharin...mentioning
confidence: 99%